Calibration of ionization chamber in megavoltage x-ray field of medical linear accelerator - Pham Hong-Lam; Hoang Thanh-Phi-Hung; Sunjun Jin; Bui Duy-Linh; Nguyen Tuan-Khai; Bui Van-Loat; Le Tuan-Anh; Nguyen Huu-Quyet; Pham Duc-Khue; Phan Viet-Cuong; Phan Tien-Dung; Pham Quang-Trung; et al. (Nuclear Technology and Radiation Protection)
Ionization chambers were calibrated regarding absorbed dose to water in MeV X-ray fields of a medical linear accelerator, with nominal maximum energies of 6 MeV and 15 MeV. Whereas, absorbed doses to water at a depth of 10 cm below the water surface were measured using the same ionization chamber (referred to as IC-1) in two different manners (i.e., applying the old beam quality correction factor kQ0 from the old IAEA/TRS-398 protocol, referred to as D1-old10 and using the new one, kQ from the updated protocol, referred to as D1-new10. The calibration factors of IC-1, ND1,D,w, Q were deduced (for beam qualities Q of MeV X-ray fields with maximum energies of 6 MeV and 15 MeV). The identical procedure was applied to two other ionization chambers (IC-i, i=2,3) to obtain absorbed doses to water at a depth of 10 cm (referred to as Di-new10) using the new beam quality correction factor. A comparison between D1-new10 and Di-new10 was conducted to derive the calibration factors of the IC-i, NiD,w,Q. The combined standard uncertainties of NiD,w,Q (i =1,2,3) were estimated within 1.22% and 2.30%, respectively.